2009
DOI: 10.1111/j.1600-0560.2008.01167.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of p63 isoforms in normal skin and hyperproliferative conditions

Abstract: Results suggest that both p63 (4A4) and p63 (H-137) can detect epidermal stem cells. But, p63 (H-137) seemed to be a better marker because p63 (H-137)-positive cells were more localized at basal layer. In addition, it can be said that p63alpha (C-12) can detect TAp63, which is important in differentiation of epidermis. Furthermore, it is concluded that molecular control of TAp63 is especially disorganized in hyperproliferative condition including psoriasis and SEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…As already mentioned, p63 is known as a putative stem cell marker of skin. In normal skin, expression of p63 was noticeable in the nuclei of cells in the basal and suprabasal layers of the epidermis . Our results revealed that GHK increased the number of p63 positive cells (Figure ).…”
Section: Discussionsupporting
confidence: 57%
“…As already mentioned, p63 is known as a putative stem cell marker of skin. In normal skin, expression of p63 was noticeable in the nuclei of cells in the basal and suprabasal layers of the epidermis . Our results revealed that GHK increased the number of p63 positive cells (Figure ).…”
Section: Discussionsupporting
confidence: 57%
“…The normal Ki-67 and p63 protein expression in the lesional skin of our patient is consistent with previous observations showing that the p63 protein is expressed in the skin despite the presence of a mutation [27][28][29]. Molecular alterations probably result in reduced transcriptional activity of the impaired p63 on several gene promoters [30][31][32][33][34][35].…”
supporting
confidence: 78%
“…However, there are no definitive markers up to date that precisely identify LSCs although a variety of LSC markers have been proposed past years. For examples, nuclear factor p63 was previously identified as a stem cell marker for keratinocytes [ 13 ]; while later studies showed that p63 was not exclusive one and it expressed more wildly not only in LSC, but also in some transit amplifying cells, especially proliferative epithelial cells during cultures [ 14 ]. More efforts are necessary for researchers to focus on the identification of new molecular factors that maintain or determine the fate of these adult stem cells.…”
Section: Introductionmentioning
confidence: 99%